Allergies and Diabetes as Risk Factors for Dengue Hemorrhagic Fever: Results of a Case Control Study - Figueiredo, Maria Aparecida A.; Rodrigues, Laura C.; Barreto, Maurício L.; Lima, José Wellington O.; Costa, Maria C. N.; Morato, Vanessa; Blanton, Ronald; Vasconcelos, Pedro F. C.; Nunes, Márcio R. T.; Teixeira, Maria Glória (PLoS neglected tropical diseases, 2010)
The physiopathology of dengue hemorrhagic fever (DHF), a severe form of Dengue Fever, is poorly understood. We are unable to identify patients likely to progress to DHF for closer monitoring and early intervention during epidemics, so most cases are sent home. This study explored whether patients with selected co-morbidities are at higher risk of developing DHF. A matched case-control study was conducted in a dengue sero-positive population in two Brazilian cities. For each case of DHF, 7 sero-positive controls were selected. Cases and controls were interviewed and information collected on demographic and socio-economic status, reported co-morbidities (diabetes, hypertension, allergy) and use of medication. Conditional logistic regression was used to calculate the strength of the association between the co-morbidities and occurrence of DHF. 170 cases of DHF and 1,175 controls were included. Significant associations were found between DHF and white ethnicity (OR = 4.70; 2.17-10.20), high income (OR = 6.84; 4.09-11.43), high education (OR = 4.67; 2.35-9.27), reported diabetes (OR = 2.75; 1.12-6.73) and reported allergy treated with steroids (OR = 2.94; 1.01-8.54). Black individuals who reported being treated for hypertension had 13 times higher risk of DHF then black individuals reporting no hypertension. This is the first study to find an association between DHF and diabetes, allergy and hypertension. Given the high case fatality rate of DHF (1-5%), we believe that the evidence produced in this study, when confirmed in other studies, suggests that screening criteria might be used to identify adult patients at a greater risk of developing DHF with a recommendation that they remain under observation and monitoring in hospital.